2016
DOI: 10.1136/bjsports-2016-096134
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of head impact exposure and brain microstructure response in a season-long application of a jugular vein compression collar: a prospective, neuroimaging investigation in American football

Abstract: BackgroundHistorical approaches to protect the brain from outside the skull (eg, helmets and mouthpieces) have been ineffective in reducing internal injury to the brain that arises from energy absorption during sports-related collisions. We aimed to evaluate the effects of a neck collar, which applies gentle bilateral jugular vein compression, resulting in cerebral venous engorgement to reduce head impact energy absorption during collision. Specifically, we investigated the effect of collar wearing during head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
72
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 53 publications
2
72
1
Order By: Relevance
“…This novel prophylaxis through venous engorgement is intriguing in its capacity to address the multiple different mechanisms of TBI on microscopic (diffuse axonal injury) and macroscopic (hemorrhage) level that lead to morbidity and mortality. 4,5,12,13 Due to the absence of acceleration injury in the CCI model, our results contest an additional mechanism elucidated by IJV compression besides slosh mitigation through venous structural alterations. A quantitative mathematical model of the complex venous network is a substantial technical challenge and is beyond the scope of this paper; however, studies of simpler geometries and loading conditions have reported that increased internal pressure, volume, and diameter increases load bearing capacity in cylindrical fluid-filled vessels.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This novel prophylaxis through venous engorgement is intriguing in its capacity to address the multiple different mechanisms of TBI on microscopic (diffuse axonal injury) and macroscopic (hemorrhage) level that lead to morbidity and mortality. 4,5,12,13 Due to the absence of acceleration injury in the CCI model, our results contest an additional mechanism elucidated by IJV compression besides slosh mitigation through venous structural alterations. A quantitative mathematical model of the complex venous network is a substantial technical challenge and is beyond the scope of this paper; however, studies of simpler geometries and loading conditions have reported that increased internal pressure, volume, and diameter increases load bearing capacity in cylindrical fluid-filled vessels.…”
Section: Discussionsupporting
confidence: 58%
“…IJV compression and, presumably its effect on brain turgor, size, and resultant slosh mitigation, has been shown in pre-clinical and clinical studies to significantly reduce microstructural axonal damage from concussive impacts and acceleration forces. 12,13,22,23 This appealing approach as a prophylactic measure to TBI can only be considered for therapeutic use if mild venous congestion is shown to not intensify hemorrhagic injury. In this experiment, we have demonstrated that IJV compression prior to injury did not increase the propensity for hemorrhagic extension; and more significantly, actually reduced hemorrhage (both subarachnoid and intraparenchymal hemorrhage) in the porcine CCI model.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of cumulative head impacts on young athletes over their entire careers are still unknown. Emerging neuroimaging investigations have generated evidence that suggests that the brain network may be affected, both structurally and functionally, during one season of contact sports, even with only nonclinical, subconcussive head impacts being tracked [Bahrami et al, ; Bazarian et al, ; Davenport et al, ; Lao et al, ; Koerte et al, ; Merchant‐Borna et al, ; Myer et al, ; Yuan et al, in press). When taken in aggregate over the career of the athlete, repetitive SCI could potentially increase the risk of season (or career) ending injuries, neurological impairments, and WM alterations [Bahrami et al, ; Myer et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Even in later adolescence, WM connectivity supporting executive control of behavior is still immature. Therefore, any compromise in WM integrity in youth or adolescence may have significant developmental implications [Asato et al, ; Bahrami et al, ; Davenport et al, ; Merchant‐Borna et al, ; Myer et al, ; Steinberg, ; ).…”
Section: Introductionmentioning
confidence: 99%
“…Two clinical studies [6,7] have used a jugular compression collar to reduce cranial slosh. They both demonstrated marked protective effects in high school athletes during competitive fullcontact play with exposure to impacts resulting in accelerations up to 200 g. Initial animal studies also lent support to the physiology of using a small jugular compressive collar in rats by providing an 83% protective effect when the animals were exposed to a 900 x g impact model [8].…”
mentioning
confidence: 99%